Rekonstruksi Stratigrafi Jalur Sungai Krenceng, Ponjong, Gunung Kidul, Yogyakarta - Rizqi, Al Hussein Flowers (ReTII, 2020)
The Stratigraphy of Southtern Mountain is one of interest object to study. One of interest area is in Tambakromo area, Ponjong, Gunung Kidul. The set of rocks along Krenceng river could be well observed by measured stratigraphy. Stratigraphy measuring section conducted in three formations and supported by paleontological and petrographical data. The aim of this research is to reconstructed the stratigraphy in research area based on detail outcrop observation. Age determination and depositional environment were interpreted for Mandalika Formation, Semilir Formation, and Wonosari Formation. The result of age determination based on foraminiferal analysis is age at N 2 – N 4 (Late Oligocene to Early Miocene) for Mandalika andesitic breccia unit. The age at N 4 – N5 (Early Miocene) is for Semilir tuffaceous lapilli unit. The Wonosari Formation was deposited at N 8 – N 10 (Middle Miocene). The depositional environment in research area started at Middle Neritic to Outer Neritic (depth of 20 to 200 metres) for Mandalika andesitic breccia unit. The tuffaceous lapiili was deposited at Middle Neritic (depth of 20 to 100 metres). The Wonosari limestone was deposited at Middle Neritic to Upper Bathyal (depth of 20 to 500 metres). Keyword: Ponjong, Stratigraphy, Mandalika, Semilir, Wonosari